Pole piece, battery and electric equipment

By constructing a gradient pore structure in the battery electrode sheet, adjusting the specific surface area, D50 and rebound rate of the active substance, the problem of difficult to take into account both the battery energy density and fast charging performance is solved, and a significant improvement in battery performance is achieved.

CN119481075APending Publication Date: 2025-02-18BEIJING ELECTRIC VEHICLE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411543793.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The energy density and fast charging performance of existing batteries are difficult to meet the high requirements of users. To improve a certain physical and chemical indicator of the active substance of the pole sheet alone can only improve the battery performance to a very small extent, and cannot take into account both the energy density and fast charging performance.

Method used

A polar sheet is proposed to form a reasonable performance parameter by constructing a good gradient pore structure, including a current collector, a first active material layer and a second active material layer, by adjusting the specific surface area, D50 and rebound rate of the active material, so as to form reasonable performance parameters to Improve battery energy density and fast charging performance.

Benefits of technology

By constructing the gradient pore structure, the energy density and fast charging performance of the battery are significantly improved, taking into account the dynamic performance and cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481075A_ABST
    Figure CN119481075A_ABST
Patent Text Reader

Abstract

The invention discloses a pole piece, a battery and electric equipment. At least one side of a current collector is provided with a first active substance layer, and a second active substance layer is arranged on the first active substance layer; the performance parameter of the first active material layer is y, the performance parameter of the second active material layer is t, y is obtained according to a formula # imgabs0 #, t is obtained according to a formula # imgabs1 #, a is the specific surface area of the active material of the first active material layer, b is the D50 of the active material of the first active material layer, c is the rebound rate when the first active material layer is coated, and c is the rebound rate when the first active material layer is coated. D is the specific surface area of the active substance of the second active substance layer, e is D50 of the active substance of the second active substance layer, and f is the rebound rate when the first active substance layer and the second active substance layer are coated; 0 < y < = 0.1, and 0.02 < t < = 0.2. Therefore, by simultaneously considering the specific surface area of the active substance, the D50 of the active substance and the rebound rate of the pole piece, a good gradient pore structure can be constructed, and the energy density and the fast charging performance of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a pole piece, a battery and an electrical device. Background Art

[0002] At present, the energy density of batteries is 170h / kg-180Wh / kg, and the fast charging capacity is 1.6C-2.6C. As people have higher and higher requirements for battery performance, the current energy density and fast charging performance of batteries are difficult to meet the requirements of users. However, by simply improving a certain physical and chemical index of the active material of the electrode (such as specific surface area, particle size, compaction density, force rebound rate, primary and secondary particle ratio, etc.), the energy density or fast charging performance of the battery can only be improved to a very small extent, and it is impossible to take both into account. Therefore, how to simultaneously improve the energy density and fast charging performance of the battery has become a technical problem that needs to be solved urgently. Summary of the invention

[0003] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, one object of the present invention is to provide a pole piece that can construct a good gradient pore structure and improve the energy density and fast charging performance of the battery.

[0004] The present invention further provides a battery having the pole piece.

[0005] The invention further provides an electrical device having the battery.

[0006] The pole piece according to the embodiment of the present invention comprises: a current collector, a first active material layer and a second active material layer. Along the thickness direction of the current collector, at least one side of the current collector is provided with the first active material layer, and the side of the first active material layer away from the current collector is provided with the second active material layer; the performance parameter of the first active material layer is y, and the performance parameter of the second active material layer is t. According to the formula Get y, according to the formula Obtain t, wherein a is the specific surface area of ​​the active material of the first active material layer, b is the D50 of the active material of the first active material layer, c is the rebound rate when the current collector is coated with the first active material layer, d is the specific surface area of ​​the active material of the second active material layer, e is the D50 of the active material of the second active material layer, and f is the rebound rate when the current collector is coated with the first active material layer and the second active material layer; satisfying the relationship: 0<y≤0.1, 0.02<t≤0.2.

[0007] According to the pole piece of the embodiment of the present invention, by simultaneously considering the specific surface area of ​​the active material, the D50 of the active material and the rebound rate of the pole piece, a good gradient pore structure can be constructed, which can improve the energy density and fast charging performance of the battery.

[0008] In some examples of the present invention, the specific surface area a of the active material in the first active material layer satisfies the relationship: 0.8 m 2 / g≤a≤1.70m 2 / g.

[0009] In some examples of the present invention, D50b of the active material of the first active material layer satisfies the relationship: 10.0 μm≤b≤17.0 μm; and / or, the rebound rate c of the current collector when coated with the first active material layer satisfies the relationship: 0.1≤c≤0.4.

[0010] In some examples of the present invention, the specific surface area d of the active material of the second active material layer satisfies the relationship: 0.90 m 2 / g≤d≤1.50m 2 / g.

[0011] In some examples of the present invention, the D50e of the active material of the second active material layer satisfies the relationship: 10.0 μm≤e≤16.0 μm, and / or the rebound rate f of the current collector when coating the first active material layer and the second active material layer satisfies the relationship: 0.1≤f≤0.3.

[0012] In some examples of the present invention, the D50 of the active material of the first active material layer is greater than the D50 of the active material of the second active material layer.

[0013] In some examples of the present invention, the rebound rate of the current collector when coating the first active material layer is greater than the rebound rate of the current collector when coating the first active material layer and the second active material layer.

[0014] In some examples of the present invention, the active material of the first active material layer and the active material of the second active material layer both include at least one of graphite, silicon, hard carbon, soft carbon, silicon carbon, tin, and lithium titanate, and the graphite includes artificial graphite and / or natural graphite.

[0015] A battery according to an embodiment of the present invention includes an electrode assembly, which includes: a first pole piece, a second pole piece and a diaphragm, the first pole piece and / or the second pole piece are the above-mentioned pole pieces, and the first pole piece, the diaphragm and the second pole piece are assembled together to form the electrode assembly.

[0016] An electric device according to an embodiment of the present invention includes the above-mentioned battery.

[0017] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0019] Figure 1 Schematic diagram of a pole piece according to an embodiment of the present invention.

[0020] Reference numerals:

[0021] Pole piece 100;

[0022] Current collector 1; first active material layer 2; second active material layer 3. DETAILED DESCRIPTION

[0023] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.

[0024] Reference below Figure 1 The electrode piece 100, a battery and an electric device according to an embodiment of the present invention are described.

[0025] like Figure 1 As shown, the pole piece 100 according to the embodiment of the present invention includes: a current collector 1 , a first active material layer 2 and a second active material layer 3 .

[0026] Among them, along the thickness direction of the pole piece 100 (ie Figure 1 The current collector 1, the first active material layer 2 and the second active material layer 3 are stacked. The current collector 1 can be copper foil, aluminum foil, composite current collector 1, etc. The current collector 1 can be used to collect and conduct current to ensure that the electrons in the battery or electrochemical device can flow smoothly. Figure 1 In the Z direction shown in the figure, a first active material layer 2 is provided on at least one side of the current collector 1, that is, a first active material layer 2 can be provided on one side of the current collector 1, or, first active material layers 2 can be provided on both sides of the current collector 1, and a second active material layer 3 is provided on the side of the first active material layer 2 facing away from the current collector 1.

[0027] The performance parameter of the first active material layer 2 is y, and the performance parameter of the second active material layer 3 is t. According to the formula Get y, according to the formula Get t, where a is the specific surface area of ​​the active material of the first active material layer 2, b is the D50 of the active material of the first active material layer 2, c is the rebound rate when the current collector 1 coats the first active material layer 2, d is the specific surface area of ​​the active material of the second active material layer 3, e is the D50 of the active material of the second active material layer 3, and f is the rebound rate when the current collector 1 coats the first active material layer 2 and the second active material layer 3.

[0028] Moreover, y satisfies the relationship: 0<y≤0.1, and t satisfies the relationship: 0.02<t≤0.2, wherein y is obtained based on the specific surface area of ​​the active material of the first active material layer 2, the D50 of the active material of the first active material layer 2, and the rebound rate when the current collector 1 coats the first active material layer 2, and t is obtained based on the specific surface area of ​​the active material of the second active material layer 3, the D50 of the active material of the second active material layer 3, and the rebound rate when the current collector 1 coats the first active material layer 2 and the second active material layer 3.

[0029] y can be any value between 0 and 0.1 (excluding 0), for example, y can be but not limited to 0.02, 0.05, 0.1, etc., t can be any value between 0.02 and 0.2 (excluding 0.02), for example, t can be but not limited to 0.05, 0.1, 0.2, etc., so that the performance parameter y of the first active material layer 2 and the performance parameter t of the second active material layer 3 can be reasonable, so that the specific surface area, D50 of the active material of each active material layer and the rebound rate of the electrode 100 coated with each active material layer can be reasonably matched, which is conducive to the transmission of lithium ions in the active material layer, can improve the fast charging performance and stable cycle performance of the battery, and can improve the energy density of the battery.

[0030] The present application provides a double-layer active material layer on at least one side of the current collector 1, which is beneficial to improving the energy density and fast charging performance of the battery. The specific surface area of ​​the active material, the D50 of the active material, and the rebound rate of the electrode 100 affect the capacity, energy density, charge and discharge performance, cycle performance and other parameters of the battery. The present application reasonably sets the performance parameter y of the first active material layer 2 and the performance parameter t of the second active material layer 3, taking into account the specific surface area of ​​the active material, the D50 of the active material, and the rebound rate of the electrode 100, so that the active sites of the first active material layer 2 and the second active material layer 3 are reasonably matched, which is conducive to the formation of a gradient pore distribution, effectively regulates the diffusion path of the active ions, and is conducive to the rapid diffusion of the active ions in the electrode 100, thereby improving the kinetic performance and energy density of the battery, and making the battery have a longer cycle life. Moreover, when the electrode 100 is constructed as a negative electrode, the liquid phase transmission resistance of the active ions released from the positive electrode on the surface of the negative electrode film layer is reduced, and will not cause accumulation on the surface to cause lithium precipitation problems. At the same time, the uniform diffusion of active ions in the film layer is conducive to reducing polarization, further improving the kinetic performance of the battery.

[0031] Therefore, by simultaneously considering the specific surface area of ​​the active material, the D50 of the active material, and the rebound rate of the electrode 100, a good gradient pore structure can be constructed, which can improve the energy density and fast charging performance of the battery.

[0032] As some embodiments of the present application, the performance parameter y of the first active material layer 2 satisfies the relationship: 0.01≤y≤0.07, that is, y can be any value between 0.01 and 0.07, for example, y can be but not limited to 0.02, 0.05, 0.07, etc. Such a setting can make the performance parameter y of the first active material layer 2 more reasonable, so that the specific surface area of ​​the active material of the first active material layer 2, the D50 of the active material and the rebound rate of the electrode 100 coated with the first active material layer 2 can be matched more reasonably, which is more conducive to the transmission of lithium ions in the first active material layer 2, can significantly improve the fast charging performance and stable cycle performance of the battery, and can significantly improve the energy density of the battery.

[0033] As some embodiments of the present application, the performance parameter y of the first active material layer 2 satisfies the relationship: 0.03≤y≤0.05, that is, y can be any value between 0.03 and 0.05, for example, y can be but not limited to 0.03, 0.04, 0.05, etc. Such a setting can more significantly improve the battery fast charging performance and stable cycle performance, and can more significantly improve the battery's energy density.

[0034] As some embodiments of the present application, the performance parameter t of the second active material layer 3 satisfies the relationship: 0.03≤t≤0.7, that is, t can be any value between 0.03 and 0.07, for example, t can be but not limited to 0.03, 0.04, 0.05, 0.07, etc. Such a setting can make the performance parameter t of the second active material layer 3 more reasonable, so that the specific surface area of ​​the active material of the second active material layer 3, the D50 of the active material and the rebound rate of the electrode 100 coated with the first active material layer 2 and the second active material layer 3 can be matched more reasonably, which is more conducive to the transmission of lithium ions in the second active material layer 3, can significantly improve the fast charging performance and stable cycle performance of the battery, and can significantly improve the energy density of the battery.

[0035] As some embodiments of the present application, the performance parameter t of the second active material layer 3 satisfies the relationship: 0.04≤t≤0.06, that is, t can be any value between 0.04 and 0.06, for example, t can be but not limited to 0.04, 0.05, 0.06, etc. Such a setting can more significantly improve the battery fast charging performance and stable cycle performance, and can more significantly improve the battery's energy density.

[0036] As some embodiments of the present application, the pole piece 100 proposed in the present application may be a positive pole piece, and the pole piece 100 proposed in the present application may also be a negative pole piece. The present application is described by taking the pole piece 100 as a negative pole piece as an example.

[0037] As some embodiments of the present application, the first active material layer 2 and the second active material layer 3 both include: active material, adhesive, and conductive agent. Among them, the conductive agent may include at least one of conductive carbon black, KS-6, acetylene black, Ketjen black, conductive fiber, graphene, conductive graphite, graphene oxide, and carbon nanotubes. For example, the conductive agent may include conductive carbon black, KS-6, and acetylene black. The conductive agent may also include conductive carbon black, Ketjen black, conductive fiber, and graphene. The conductive agent may also include acetylene black, conductive graphite, graphene oxide, and carbon nanotubes. In this way, the materials included in the conductive agent can be selected according to the needs of the product, which is conducive to improving the selectivity of the conductive agent. In addition, by making the conductive agent include multiple materials at the same time, the charge and discharge performance can be improved.

[0038] The binder may include at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyethyleneimine, polyaniline, polyacrylic acid, sodium alginate, styrene-butadiene rubber, sodium carboxymethyl cellulose, phenolic resin, and epoxy resin. For example, the binder may include polyvinylidene fluoride, polytetrafluoroethylene, and polyethyleneimine. The binder may also include polyaniline, polyacrylic acid, and sodium alginate. In this way, the materials included in the binder can be selected according to the requirements of the product, which is beneficial to improving the selectivity of the binder. In addition, by making the binder include multiple materials at the same time, the bonding performance can be improved.

[0039] The active material may include at least one of graphite, silicon, hard carbon, soft carbon, silicon carbon, tin, lithium titanate, and mesophase carbon microspheres, wherein the graphite includes artificial graphite and / or natural graphite. For example: the active materials all include graphite, silicon, and hard carbon, or the active materials all include soft carbon, silicon carbon, tin, and lithium titanate, or the active materials all include graphite, tin, and lithium titanate. The materials included in the active materials can be selected according to the requirements of the product to improve the selectivity of the active materials, and by making the active materials include a variety of materials, it is beneficial to improve the charge and discharge performance of the battery.

[0040] In some embodiments of the present invention, the specific surface area a of the active material in the first active material layer 2 satisfies the relationship: 0.8 m 2 / g≤a≤1.70m 2 / g. That is, the specific surface area a of the active material in the first active material layer 2 can be 0.8 m 2 / g to 1.70m 2 / g, for example, the specific surface area a of the active material in the first active material layer 2 may be, but is not limited to, 0.8 m 2 / g, 1.1m 2 / g, 1.4m 2 / g, 1.7m 2 This arrangement can make the specific surface area of ​​the active material of the first active material layer 2 reasonable, improve the electrochemical performance of the electrode 100, reduce internal resistance, increase capacity, and improve cycle performance and rate performance.

[0041] As some embodiments of the present application, the specific surface area a of the active material in the first active material layer 2 satisfies the relationship: 1.15 m 2 / g≤a≤1.55m 2 / g. That is, the specific surface area a of the active material in the first active material layer 2 can be 1.15 m 2 / g to 1.55m 2 / g, for example, the specific surface area a of the active material in the first active material layer 2 may be, but is not limited to, 1.15 m 2 / g, 1.25m 2 / g, 1.45m 2 / g, 1.55m 2 This arrangement can make the specific surface area of ​​the active material of the first active material layer 2 more reasonable, can significantly improve the electrochemical performance of the electrode 100, can significantly reduce the internal resistance, increase the capacity, and improve the cycle performance and rate performance.

[0042] As some embodiments of the present application, the specific surface area a of the active material of the first active material layer 2 satisfies the relationship: 1.30 m 2 / g≤a≤1.40m 2 / g. That is, the specific surface area a of the active material in the first active material layer 2 may be, but is not limited to, 1.30 m 2 / g to 1.40m 2 / g, for example, the specific surface area a of the active material in the first active material layer 2 may be, but is not limited to, 1.30 m 2 / g, 1.35m 2 / g, 1.40m 2 / g, etc. Such a configuration can significantly improve the electrochemical performance of the electrode 100, and can significantly reduce the internal resistance, increase the capacity, and improve the cycle performance and rate performance.

[0043] In some embodiments of the present invention, the D50b of the active material of the first active material layer 2 satisfies the relationship: 10.0μm≤b≤17.0μm. That is, the D50b of the active material of the first active material layer 2 can be any value between 10μm and 17μm. For example, the D50 of the active material of the first active material layer 2 can be but not limited to 10μm, 12μm, 15μm, 17μm, etc. Such a setting can make the D50 of the first active material layer 2 reasonable, can improve the rate performance of the battery, and can take into account the processing performance and electrochemical performance of the electrode 100, which can improve the performance of the battery.

[0044] As some embodiments of the present application, the D50b of the active material of the first active material layer 2 satisfies the relationship: 11.0μm≤b≤13.0μm. That is to say, the D50b of the active material of the first active material layer 2 can be any value between 11μm and 13μm. For example, the D50 of the active material of the first active material layer 2 can be but not limited to 11μm, 12μm, 13μm, etc. Such a setting can make the D50 of the first active material layer 2 more reasonable, can significantly improve the rate performance of the battery, and can effectively take into account the processing performance and electrochemical performance of the electrode 100, which can significantly improve the performance of the battery.

[0045] As some embodiments of the present application, the D50b of the active material of the first active material layer 2 satisfies the relationship: 11.0μm≤b≤12.0μm. That is, the D50b of the active material of the first active material layer 2 can be any value between 11μm and 12μm. For example, the D50 of the active material of the first active material layer 2 can be but not limited to 11μm, 11.5μm, 12μm, etc. Such a setting can more significantly improve the rate performance of the battery, and can make the electrode 100 have excellent processing performance and electrochemical performance.

[0046] In some embodiments of the present invention, the rebound rate c of the current collector 1 when coating the first active material layer 2 satisfies the relationship: 0.1≤c≤0.4, that is, the rebound rate c of the current collector 1 when coating the first active material layer 2 can be any value between 0.1 and 0.4. For example, the rebound rate c of the current collector 1 when coating the first active material layer 2 can be but not limited to 0.1, 0.2, 0.3, 0.4, etc. This setting can make the rebound rate c of the current collector 1 when coating the first active material layer 2 reasonable, and can make the battery have a higher actual capacity, good stability performance and a longer service life. In addition, the rebound rate affects the porosity. Such a setting can make the electrode 100 have good wettability, and can make the battery have good fast charging performance.

[0047] As some embodiments of the present application, the rebound rate c when the current collector 1 is coated with the first active material layer 2 satisfies the relationship: 0.14≤c≤0.35, that is, the rebound rate c when the current collector 1 is coated with the first active material layer 2 can be any value between 0.14 and 0.35. For example, the rebound rate c when the current collector 1 is coated with the first active material layer 2 can be but not limited to 0.14, 0.24, 0.3, 0.35, etc. This setting can make the rebound rate c when the current collector 1 is coated with the first active material layer 2 more reasonable, and can make the battery have high actual capacity, excellent stability performance and excellent service life. In addition, the rebound rate affects the porosity. Such a setting can make the electrode 100 have excellent wettability, and can make the battery have excellent fast charging performance.

[0048] As some embodiments of the present application, the rebound rate c when the current collector 1 is coated with the first active material layer 2 satisfies the relationship: 0.20≤c≤0.30, that is, the rebound rate c when the current collector 1 is coated with the first active material layer 2 can be any value between 0.2 and 0.3, for example, the rebound rate c when the current collector 1 is coated with the first active material layer 2 can be but not limited to 0.2, 0.25, 0.3, etc. Such a setting can make the battery have a high actual capacity, more excellent stability performance and service life, and can significantly improve the fast charging performance of the battery.

[0049] In some embodiments of the present invention, the specific surface area d of the active material of the second active material layer 3 satisfies the relationship: 0.90 m 2 / g≤d≤1.50m 2 / g. That is, the specific surface area d of the active material in the second active material layer 3 can be 0.90 m 2 / g to 1.50m 2 / g, for example, the specific surface area d of the active material in the second active material layer 3 may be, but is not limited to, 0.90 m 2 / g, 1.00m 2 / g, 1.30m 2 / g, 1.50m 2 This arrangement can make the specific surface area of ​​the active material of the second active material layer 3 more reasonable, can significantly improve the electrochemical performance of the electrode 100, can significantly reduce the internal resistance, increase the capacity, and improve the cycle performance and rate performance.

[0050] As some embodiments of the present application, the specific surface area d of the active material of the second active material layer 3 satisfies the relationship: 1.00 m 2 / g≤d≤1.30m 2 / g. That is, the specific surface area d of the active material in the second active material layer 3 can be 1.00 m 2 / g to 1.30m 2 / g, for example, the specific surface area d of the active material in the second active material layer 3 may be, but is not limited to, 1.00 m 2 / g, 1.10m 2 / g, 1.20m 2 / g, 1.30m 2 This arrangement can make the specific surface area of ​​the active material of the second active material layer 3 more reasonable, can significantly improve the electrochemical performance of the electrode 100, can significantly reduce the internal resistance, increase the capacity, and improve the cycle performance and rate performance.

[0051] As some embodiments of the present application, the specific surface area d of the active material of the second active material layer 3 satisfies the relationship: 1.05m 2 / g≤d≤1.20m 2 / g. That is, the specific surface area d of the active material in the second active material layer 3 can be 1.05m 2 / g to 1.20m 2 / g, for example, the specific surface area d of the active material in the second active material layer 3 may be, but is not limited to, 1.05 m 2 / g, 1.10m 2 / g, 1.20m 2 / g, etc. Such a configuration can significantly improve the electrochemical performance of the electrode 100, and can significantly reduce the internal resistance, increase the capacity, and improve the cycle performance and rate performance.

[0052] In some embodiments of the present invention, the D50e of the active material of the second active material layer 3 satisfies the relationship: 10.0μm≤e≤16.0μm. That is, the D50e of the active material of the second active material layer 3 can be any value between 10μm and 16μm. For example, the D50 of the active material of the second active material layer 3 can be but not limited to 10μm, 12μm, 15μm, 16μm, etc. Such a setting can make the D50 of the second active material layer 3 reasonable, can improve the rate performance of the battery, and can take into account the processing performance and electrochemical performance of the electrode sheet 100, which can improve the performance of the battery.

[0053] As some embodiments of the present application, the D50e of the active material of the second active material layer 3 satisfies the relationship: 11.0μm≤e≤14.0μm. That is to say, the D50e of the active material of the second active material layer 3 can be any value between 11μm and 14μm. For example, the D50 of the active material of the second active material layer 3 can be but not limited to 11μm, 12μm, 13μm, 14μm, etc. Such a setting can make the D50 of the second active material layer 3 more reasonable, can significantly improve the rate performance of the battery, and can effectively take into account the processing performance and electrochemical performance of the electrode sheet 100, which can significantly improve the performance of the battery.

[0054] As some embodiments of the present application, the D50e of the active material of the second active material layer 3 satisfies the relationship: 11.5μm≤e≤12.5μm. That is, the D50e of the active material of the second active material layer 3 can be any value between 11.5μm and 12.5μm. For example, the D50 of the active material of the second active material layer 3 can be but not limited to 11.5μm, 12μm, 12.5μm, etc. Such a setting can more significantly improve the rate performance of the battery, and can make the electrode 100 have excellent processing performance and electrochemical performance.

[0055] In some embodiments of the present invention, the rebound rate f when the current collector 1 is coated with the first active material layer 2 and the second active material layer 3 satisfies the relationship: 0.1≤f≤0.3, that is, the rebound rate f when the current collector 1 is coated with the first active material layer 2 and the second active material layer 3 can be any value between 0.1 and 0.3. For example, the rebound rate f when the current collector 1 is coated with the first active material layer 2 and the second active material layer 3 can be but not limited to 0.1, 0.2, 0.3, etc. This arrangement can make the rebound rate f when the current collector 1 is coated with the first active material layer 2 and the second active material layer 3 reasonable, so that the battery has a higher actual capacity, good stability and a longer service life. In addition, the rebound rate affects the porosity. This arrangement can make the electrode 100 have good wettability and the battery have good fast charging performance.

[0056] As some embodiments of the present application, the rebound rate f when the current collector 1 is coated with the first active material layer 2 and the second active material layer 3 satisfies the relationship: 0.1≤f≤0.2, that is, the rebound rate f when the current collector 1 is coated with the first active material layer 2 and the second active material layer 3 can be any value between 0.1 and 0.2. For example, the rebound rate f when the current collector 1 is coated with the first active material layer 2 and the second active material layer 3 can be but not limited to 0.1, 0.15, 0.2, etc. This arrangement can make the rebound rate c when the current collector 1 is coated with the first active material layer 2 and the second active material layer 3 more reasonable, and can make the battery have high actual capacity, excellent stability performance and excellent service life. In addition, the rebound rate affects the porosity. Such an arrangement can make the electrode 100 have excellent wettability, and can make the battery have excellent fast charging performance.

[0057] As some embodiments of the present application, the rebound rate f when the current collector 1 is coated with the first active material layer 2 and the second active material layer 3 satisfies the relationship: 0.21≤f≤0.16, that is, the rebound rate f when the current collector 1 is coated with the first active material layer 2 and the second active material layer 3 can be any value between 0.12 and 0.16. For example, the rebound rate f when the current collector 1 is coated with the first active material layer 2 and the second active material layer 3 can be but not limited to 0.12, 0.14, 0.16, etc. Such a setting can make the battery have a high actual capacity, more excellent stability performance and service life, and can significantly improve the fast charging performance of the battery.

[0058] It should be noted that the smaller the particle size of the active material, the higher the surface energy of the particles, the easier it is to agglomerate and react with the electrolyte, and the smaller the particle size of the active material, the larger the initial capacity of the active material layer, which is beneficial to the insertion and extraction of Li+, and is beneficial to improving the rate performance of the battery. However, if the particle size of the active material is too small, the internal resistance of the battery will increase, and too much energy will accumulate during the charging and discharging process, and the temperature will increase, which will lead to safety hazards. Moreover, if the particle size of the active material is too small, the irreversible capacity is also large. The present application can reasonably design the D50 of the active material of the first active material layer 2 and the D50 of the active material of the second active material layer 3, while making the active material layer have a larger initial capacity and the battery have a high rate performance, reduce the safety hazards caused by the excessive internal resistance of the battery, and make the irreversible capacity smaller, so that the battery can have excellent performance.

[0059] In some embodiments of the present invention, the D50 of the active material in the first active material layer 2 is greater than the D50 of the active material in the second active material layer 3. It should be noted that when the D50 of the active material in the first active material layer 2 is greater than the D50 of the active material in the second active material layer 3, the fine powder content in the active material in the first active material layer 2 and the second active material layer 3 can be well matched, and the degree of matching with the concentration gradient distribution of the active ions during the battery charging and discharging process is good, which effectively adjusts the diffusion rate of the active ions inside different particles, and can effectively improve the fast charging performance of the battery. In addition, the particle size of the active material in the first active material layer 2 is larger, and there are more vacancies that can receive active ions, which is conducive to the improvement of energy density. At the same time, the particle size of the active material in the second active material layer 3 is smaller, and the binder has more attachment sites on its surface. The particle crushing degree is smaller during the cold pressing treatment, and the probability of the material generating a new surface is lower. Therefore, it has a stronger ability to conduct electrons during the charging and discharging process, and can effectively inhibit the bridge breaking phenomenon of the electrolyte, which can further improve the cycle life.

[0060] In some embodiments of the present invention, the rebound rate of the current collector 1 when coated with the first active material layer 2 is greater than the rebound rate of the current collector 1 when coated with the first active material layer 2 and the second active material layer 3. Such a setting can form a gradient pore structure, which can significantly improve the energy density and fast charging performance of the battery.

[0061] The following description will be made by taking the electrode sheet 100 proposed in the present application as a negative electrode sheet as an example.

[0062] The specific preparation scheme of the negative electrode sheet 100 and the lithium ion battery including the negative electrode sheet is as follows:

[0063] (1) Preparation of negative electrode

[0064] A 6μm copper foil is used as the current collector 1 of the negative electrode sheet, and the first active material layer 2 and the second active material layer 3 are uniformly coated on the surface of the copper foil at the same time, and then the negative electrode sheet is obtained by cold pressing. Among them, the first active material layer 2 is composed of 96.3wt%-97.1wt% of artificial graphite, 0wt%-0.5wt% of SP, 0.7wt%-1.5wt% of PAA, 0.5wt%-1.0wt% of carboxymethyl cellulose, and 0.4-1.5wt% of styrene-butadiene rubber. The overall thickness of the negative electrode sheet is 120μ-155μm.

[0065] (2) Application of negative electrode

[0066] The above negative electrode sheet was prepared into a lithium-ion battery, and the battery energy density and fast charging rate were tested.

[0067] Preparation of the positive electrode:

[0068] A 15 μm aluminum foil is used as the current collector 1, and the positive electrode active slurry is evenly coated on the surface of the aluminum foil, and then cold pressed to obtain a positive electrode sheet. The positive electrode active slurry is composed of 96.7 wt% to 97 wt% of lithium iron phosphate material, 0.8 wt% to 1.1 wt% of SP, 0.7 wt% to 1.0 wt% of CNTs, and 0 wt% to 1.8 wt% of PVDF. The overall thickness of the positive electrode sheet is 172 μm to 222 μm.

[0069] Preparation and testing of lithium-ion batteries:

[0070] The positive electrode sheet, the coated separator, and the negative electrode sheet are stacked in a Z-shaped manner to obtain a stacking unit. The stacking unit is then thermally compounded under the conditions of a pressure of 0.62MPa-0.68MPa, a temperature of 80℃-86℃, and a time of 1min-5min. Then, the steps of shelling, baking, liquid injection, formation, high-temperature storage, capacity division, high-temperature aging, and room-temperature aging are performed to finally obtain a lithium-ion battery.

[0071] Battery energy density test: After the battery is left to stand at 25℃±2℃ for 30 minutes, it is charged to 3.65V at a constant current of 1C, and then charged to 0.05C current cutoff at a constant voltage; left for 30 minutes; then discharged to 2.5V at a constant current of 1C; cycle 3 times, take the discharge energy of the last cycle of the battery cell, calculated as E (Wh); weigh the battery cell with an electronic balance, calculated as W (kg), and calculate the energy density ED = E / W (Wh / kg).

[0072] Battery fast charging capability test: After the battery is left standing at 25℃±2℃ for 30 minutes, it is discharged to 2.5V at a constant current of 1C; it is left for 30 minutes; it is charged to 3.65V at a constant current of 3C or 4C, and then it is charged at a constant voltage to a current cutoff of 0.05C; the constant current ratio is calculated as constant current charging capacity / total charging capacity*100%.

[0073] The data of the embodiments and comparative examples are shown in the following table:

[0074]

[0075] Combined with the data in the above table, it can be seen that when the first active material layer 2 and the second active material layer 3 both meet the conditions specified in this application, the performance is excellent.

[0076] According to an embodiment of the present invention, the battery includes an electrode assembly, which includes: a first electrode piece, a second electrode piece and a diaphragm. The first electrode piece and / or the second electrode piece is the above-mentioned electrode piece 100. The first electrode piece, the diaphragm and the second electrode piece are assembled together to form an electrode assembly. By simultaneously considering the specific surface area of ​​the active material, the D50 of the active material and the rebound rate of the electrode piece 100, a good gradient pore structure can be constructed, which can improve the energy density and fast charging performance of the battery.

[0077] According to the electrical equipment of the embodiment of the present invention, including the above-mentioned battery, a good gradient pore structure can be constructed by simultaneously considering the specific surface area of ​​the active material, the D50 of the active material and the rebound rate of the electrode 100, which can improve the energy density and fast charging performance of the battery.

[0078] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.

[0079] In the description of the present invention, "first feature" or "second feature" may include one or more of the features.

[0080] In the description of the present invention, "plurality" means two or more.

[0081] In the description of the present invention, a first feature being “on” or “under” a second feature may include that the first and second features are directly in contact with each other, or may include that the first and second features are not in direct contact with each other but are in contact with each other via another feature therebetween.

[0082] In the description of the present invention, "above", "over" and "on" a first feature includes the first feature being directly above and obliquely above the second feature, or simply means that the first feature is horizontally higher than the second feature.

[0083] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0084] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.

Claims

1. A pole piece (100), characterized in that: include: A current collector (1), a first active material layer (2) and a second active material layer (3), wherein along the thickness direction of the current collector (1), the first active material layer (2) is provided on at least one side of the current collector (1), and the second active material layer (3) is provided on a side of the first active material layer (2) facing away from the current collector (1); The performance parameter of the first active material layer (2) is y, and the performance parameter of the second active material layer (3) is t. According to the formula Get y, according to the formula Obtain t, wherein a is the specific surface area of ​​the active material of the first active material layer (2), b is the D50 of the active material of the first active material layer (2), c is the rebound rate when the current collector (1) is coated with the first active material layer (2), d is the specific surface area of ​​the active material of the second active material layer (3), e is the D50 of the active material of the second active material layer (3), and f is the rebound rate when the current collector (1) is coated with the first active material layer (2) and the second active material layer (3); The relationship is satisfied: 0<y≤0.1, 0.02<t≤0.

2.

2. The pole piece (100) according to claim 1, characterized in that: The specific surface area a of the active material of the first active material layer (2) satisfies the relationship: 0.8 m 2 / g≤a≤1.70m 2 / g.

3. The pole piece (100) according to claim 1, characterized in that: The D50b of the active material of the first active material layer (2) satisfies the relationship: 10.0 μm ≤ b ≤ 17.0 μm; And / or, the rebound rate c of the current collector (1) when coated with the first active material layer (2) satisfies the relationship: 0.1≤c≤0.

4.

4. The pole piece (100) according to claim 1, characterized in that: The specific surface area d of the active material of the second active material layer (3) satisfies the relationship: 0.90 m 2 / g≤d≤1.50m 2 / g.

5. The pole piece (100) according to claim 1, characterized in that: The D50e of the active material of the second active material layer (3) satisfies the relationship: 10.0 μm ≤ e ≤ 16.0 μm; And / or, the rebound rate f of the current collector (1) when coating the first active material layer (2) and the second active material layer (3) satisfies the relationship: 0.1≤f≤0.

3.

6. The pole piece (100) according to claim 1, characterized in that: The D50 of the active material in the first active material layer (2) is greater than the D50 of the active material in the second active material layer (3).

7. The pole piece (100) according to claim 1, characterized in that: The rebound rate of the current collector (1) when coated with the first active material layer (2) is greater than the rebound rate of the current collector (1) when coated with the first active material layer (2) and the second active material layer (3).

8. The pole piece (100) according to any one of claims 1 to 7, characterized in that: The active material of the first active material layer (2) and the active material of the second active material layer (3) both include at least one of graphite, silicon, hard carbon, soft carbon, silicon carbon, tin, and lithium titanate, and the graphite includes artificial graphite and / or natural graphite.

9. A battery, characterized in that: The invention comprises an electrode assembly, wherein the electrode assembly comprises: a first pole piece, a second pole piece and a diaphragm, wherein the first pole piece and / or the second pole piece is a pole piece (100) according to any one of claims 1 to 8, and the first pole piece, the diaphragm and the second pole piece are assembled together to form the electrode assembly.

10. An electrical device, characterized in that: Comprising a battery according to claim 9.